2021
DOI: 10.35995/tmj20210201
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Valvular Oxidative Stress in a Young Patient with Primary Severe Mitral Regurgitation

Abstract: Mitral valve regurgitation (MR) is the most common valvular heart disease. Diagnosing and managing mitral regurgitation is often challenging and requires a structured approach, integrating findings on history, physical examination and imaging. A common cardiac anomaly is myxomatous mitral valve prolapse. Excess myxomatous leaflet tissue, bileaflet prolapse or billowing, chordae elongation and annular dilatation are all features of Barlow’s disease. Currently, there is no successful pharmacological treatment av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The group of Donald Heistad firstly reported that oxidative stress was increased in calcified regions of stenotic aortic valves removed during surgical valvular replacement due to the dysregulation of the antioxidant defense [5]. We have previously reported an increase in local ROS at the level of the diseased mitral valve harvested during surgical replacement from a young patient with primary severe mitral regurgitation; interestingly, the magnitude of oxidative was mitigated after treating the sample with an angiotensin II type 1 (AT1) receptor antagonist [6].…”
Section: Introductionmentioning
confidence: 99%
“…The group of Donald Heistad firstly reported that oxidative stress was increased in calcified regions of stenotic aortic valves removed during surgical valvular replacement due to the dysregulation of the antioxidant defense [5]. We have previously reported an increase in local ROS at the level of the diseased mitral valve harvested during surgical replacement from a young patient with primary severe mitral regurgitation; interestingly, the magnitude of oxidative was mitigated after treating the sample with an angiotensin II type 1 (AT1) receptor antagonist [6].…”
Section: Introductionmentioning
confidence: 99%